Governing the city through im/mobilities during COVID-19 – technological self-governance. Issue 4 (4th July 2021) - Shin, HaeRan
ABSTRACT: By exploring im/mobilities during the COVID-19 pandemic, this paper theorizes its effects on the interplay between mobility and governance as well as contributing to debates on the city, power, and spatial strategy. To explain governing power in the rearrangement of im/mobilities and urban life during the pandemic, the paper employs the concept of "governmobility." The term refers to governing through (im)mobility, and the technological self-governance discussed is not only constituted by the internalized regulation of im/mobilities but more specifically those mobilities enacted through communication technologies facilitating collective relations. This paper argues that technological self-governance maintains governmobility by enabling people to adjust to their "new normal" and continue with their daily lives. Governing, norm-making, and places are interwoven in the city's im/mobility regime, and resistance and criticism are intrinsic in the process of forming governance. The paper suggests considering place-(re)making at various levels as a proactive response to the new norm. Place-(re)making is constituted by governing activities of state and market as well as citizens to reshape their society and space.